1995
DOI: 10.1074/jbc.270.26.15858
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neurite Outgrowth and SNAP-25 Gene Expression by the Brn-3a Transcription Factor

Abstract: SNAP-25 is a presynaptic nerve terminal protein which is also essential for the process of neurite outgrowth in vivo and in vitro. However the processes regulating its expression have not been characterized previously. We show that the gene encoding this protein, SNAP, is strongly activated by the Brn-3a POU (Pit-Oct-Unc) family transcription factor. Expression of both Brn-3a and SNAP-25 increases when ND7 neuronal cells are induced to extend neurite processes by serum removal. Inhibition of Brn-3a expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…In contrast, the only other known target for activation by Brn-3b, the nicotinic acetylcholine receptor α2 subunit gene is not activated by the isolated POU domain of Brn-3b. 26 This is similar to observations with the related Brn-3a factor, where some genes are activated by the isolated POU domain alone [23][24][25] whereas others require additional N-terminal sequences. 35,36 Whatever the case, the data presented here identify CDK4 as a target for transcriptional activation by Brn-3b.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In contrast, the only other known target for activation by Brn-3b, the nicotinic acetylcholine receptor α2 subunit gene is not activated by the isolated POU domain of Brn-3b. 26 This is similar to observations with the related Brn-3a factor, where some genes are activated by the isolated POU domain alone [23][24][25] whereas others require additional N-terminal sequences. 35,36 Whatever the case, the data presented here identify CDK4 as a target for transcriptional activation by Brn-3b.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, although Brn-3b can activate the promoter of the nicotinic acetylcholine receptor α2 subunit gene. 26 Brn-3b represses the expression of a variety of genes involved in neuronal differentiation including SNAP-25 24 and the neurofilaments 25 and thereby represses neuronal differentiation itself. 27 Our initial studies in breast cancer cells, identified the BRCA-1 gene as a target for transcriptional repression by Brn-3b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Brn-3a can directly activate the promoters of genes that are associated with protection against apoptosis (Bcl-2 and Bcl-X L ) and differentiation (e.g. in structural genes such as ␣-internexin (13), neurofilament (9), receptors such as neurotrophin receptor TrkA (14), and synaptic genes such as SNAP-25 (15) and synaptophysin (16)). In addition to direct effects, Brn-3a can also modify gene transcription indirectly by interaction with cellular proteins such as p53, thus effectively increasing the range of target genes regulated by this transcription factor.…”
mentioning
confidence: 99%
“…In agreement with this idea the three members of the Brn-3 family are expressed in distinct but overlapping populations of neuronal cells during development and in the adult organism (1)(2)(3)(4)(5)11) with Brn-3a for example being expressed in the first differentiated neurons to appear in the midbrain, hindbrain, and spinal cord during development (12). Interestingly Brn-3a has been shown in co-transfection experiments to activate several promoters including those of the neuronally expressed genes encoding pro-opiomelancortin (1), ␣-internexin (13), and the presynaptic vesicle protein SNAP-25 (14) as well as a thymidine kinase (tk) 1 promoter containing an added synthetic binding site for the various forms of Brn-3 (tk-Oct) (15,18). In contrast Brn-3b represses these promoters (13,15,18) and also inhibits their activation by Brn-3a.…”
mentioning
confidence: 99%